Influence of acute fasting on pain tolerance in healthy subjects: a randomised crossover study - Edwards, Sophie A.; Martin, Sarah L.; Rainey, Timothy; Whitaker, Grace; Greenwood, Darren C.; Jones, Anthony; Sivan, Manoj (Frontiers in Pain Research, 2023)
Background Although chronic pain and obesity are global health crises with substantial healthcare costs, little is known about the relationship between pain perception and eating behaviours. Food consumption has been reported to provide an analgesic effect by the release of neurotransmitters modulating the pain network. However, whether short-term (acute) fasting affects pain perception remains unclear. Purpose This study aimed to investigate the effect of acute fasting on pain perception and whether attention and mood changes drove the observed changes. Patients and methods The cold pressor test (CPT) was used to investigate the pain tolerance of 25 healthy participants in both non-fasting and 12-h fasting sessions. They were randomised to either session with a crossover to the other after at least 24 h, with the experimenter blinded to the sessions. The pain tolerance was measured using a Stroop task in both attentive and distracted states. The Profile of Mood States (POMS) questionnaire was used to capture the mood, and a 10-point hunger scale was used to measure hunger. Mixed-effects models were used to investigate the influence of fasting and distraction on pain perception, accounting for the repeated measures. Results Fasting reduced CPT pain tolerance, with fasting participants twice as likely to withdraw their hands early (hazard ratio = 2.4, 95% CI: 1.3–4.5). Though men tolerated CPT pain longer than women, there was no evidence that men responded to fasting differently than women (p = 0.9). In addition, no evidence supporting that fasting affected attention or mood was found. Nonetheless, it increased hunger scores by 2.7 points on a 10-point scale (95% CI: 1.2–4.2) and decreased blood glucose concentration levels by 0.51 mmol/L (95% CI: 0.19–0.84). Conclusion Acute fasting reduces pain tolerance in the healthy participants, and this effect is independent of gender and attention or mood changes.